Funkcjonowanie nadnerczy u pacjentów pediatrycznych podczas leczenia onkologicznego i po jego zakończeniu - Hull, Barbara; Wedrychowicz, Anna (Pediatric Endocrinology Diabetes and Metabolism, 2022)
The purpose of this work was to present the current state of knowledge on the effects of frequently used therapeutic forms, selected pharmacotherapy (including glucocorticosteroids, immune checkpoint inhibitors, mitotane, metyrapone, aminoglutetimide, etomidate, ketoconazole, fluconazole), but also radiation therapy on the functioning of the hypothalamic-pituitary-adrenal axis in children and adolescent during and after oncological treatment. The most common pediatric cancers, where complications of adrenal insufficiency occur, are presented. Moreover, current recommendations how to diagnose the function of the adrenal axis in oncological pediatric patients, as well during oncological treatment as after it, including patients treated with steroids and also patients in severe stages, are reported. The rules of the treatment of adrenal dysfunction in those patients are presented. This understanding is of key importance for oncologists and endocrinologists in the process of diagnosing, treating and developing patient health care, as well as during therapy as after it, offering safety and improving the quality of life.